Effect of multiphase internal flows considering hydrate phase transitions on the streamwise oscillation of marine risers. (1st February 2020) - Lou, Min; Liang, Weixing
Abstract: Marine risers are the main transportation channels of offshore oil and gas from the wellheads to the floating platforms. In mixed oil and gas transportation, natural gas hydrates are produced at low temperatures and high pressures, which makes the multiphase internal flow quite complex. In order to explore the effects of multiphase internal flows considering hydrate phase transitions on the streamwise oscillation of marine risers, a numerical multiphase internal flow model considering hydrate phase transitions is established, where the flow parameters are solved with the finite difference method. Subsequently, based on the virtual work principle, a non-linear vibration equation for marine risers is deduced. The parameters of the multiphase internal flow are introduced and solved numerically with the finite element method. The results show that the gas pressure and density decrease, and the gas velocity and acceleration increase, from the riser inlet to the outlet due to gas expansion and the hydrate phase transitions. The natural frequencies of the riser increase with an increase of gas intake, and the changing trends at higher modes are more obvious. Under current excitation, the amplitude envelope of the riser decreases with an increase of gas intake. Under wave excitation, the gas intake has little effect on the vibration frequency of the riser. However, when gas intake changes, the natural frequency of the riser changes, which leads to a change of the resonance amplification coefficient, thus affecting the vibration amplitude of the riser. Highlights: A multiphase internal flow model by considering hydrate phase transitions was established. The parameters of the multiphase internal flows are introduced into the vibration equation of the riser. The effect of multiphase internal flows on the natural frequencies and streamwise oscillation of the riser is studied.